Lost in the war - Antle, Nancy (New York : Puffin Books, 2000)
Twelve-year-old Lisa Grey struggles to cope with a mother whose traumatic experiences as a nurse in Vietnam during the war are still haunting her.
Keywords: Vietnam War, 1961-1975 -- Juvenile fiction